PENGARUH SLOW DEEP BREATHING TERHADAP TEKANAN DARAH LANSIA PENDERITA HIPERTENSI DI PUSKESMAS MANUTAPEN-KOTA KUPANG - Riantiarno, Flavianus; Da Gosta, Brigida M; Alabhari, Rishan; Merlin, Ni Made (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hypertension is a problem that often occurs in society. Hypertension is common in the elderly. Hypertension, which is not suffered by the elderly, can cause various conditions for the elderly and affect the quality of life of the elderly. There needs to be treatment. One of them with relaxation therapy. The research design used experimental quasy with a pretest and posttest group design approach. The population of this study was the elderly with hypertension at the Manutapen Health Center, with a total sample of 23 respondents. The sampling method is purposive sampling. The results of the analysis using the Wilxocon test, obtained the p-value of systolic blood pressure: 0.000 and diastolic blood pressure: 0.000. This shows that slow deep breathing has an effect on reducing systolic and diastolic blood pressure in people with hypertension. The conclusion is that Slow Deep Breathing affects the blood pressure of the elderly with hypertension.